Verificação de características eletroacústicas: estudo comparativo entre softwares de fabricantes de aparelhos de amplificação sonora individual - Rezende, Juliana Sanches (2009)
Introduction: The national hearing health policy in Brazil has made hearing aids available to hearing impaired children and adults and, therefore, the audiologist responsible for dispensing them has to deal with a number of different manufactures for different types and degrees of hearing losses. Goal: To compare the prescribed electroacustic characteristics and modifications suggested for acclimatization among software of different hearing aids manufactures. Method: Six simulated cases of sensorineural hearing losses three adults and three children, including three degrees of loss for each age, were analyzed (P45, P65 e P80). For all cases, a flat configuration was assumed. Three softwares of hearing aids brands were chosen, based on the following criteria: software NOAH 3.0 with the choice for NAL-NL1 and DSL [i/o]v4.1; availability of measurements for output at the 2cc coupler for different intensities of input signal. Procedures: - Verification of output values with the 2cc coupler when compared with the values presented for each brand software, for each hearing loss, using NAL-NL1 for adults and DSL [i/o] v.4.1 for children. Verification of output values prescribed by the original DSL[i/o] v.4.1, as compared with those prescribed by the manufacturer software considering level of acclimatization. Results: A large variation of the amplification provided by the hearing aids for children and adults was found, considering different levels of hearing loss, in most frequencies, for different input levels. This variation was between -3 and -28 dBNPS in high frequencies, comparing the DSL[i/o]v4.1 manufacturer method and the original one. Conclusion: The results of this study have revealed the verification of the electroacoustic characteristics of the hearing aids during the fitting process, ensuring the patient, especially children, a more appropriate amplification